Rice and roots food terminal planning for staple and major agricultural commodities In San Rafael, Bulacan - Berba, Leandro Lorenzo C. (College of Architecture, University of the Philippines Diliman, 2025)
The study examines how food terminal planning improves agricultural logistics, strengthens market accessibility, and supports local food systems. The research initially assessed potential sites across District III, Bulacan, using systematic criteria to determine viability. Through further refinement, San Rafael emerged as the most suitable location, allowing for a detailed analysis while maintaining relevance to broader regional applications. The study highlights the importance of aligning infrastructure planning with stakeholder-driven approaches to ensure that food terminals effectively address local agricultural and market challenges. Additionally, findings emphasize the role of food terminals in fostering consumer engagement by providing direct access to locally sourced produce and reinforcing agriculture’s socio-economic significance. Spatial planning methodologies, particularly site selection and accessibility assessments, help structure logistical efficiency while ensuring adaptability. By narrowing the study’s focus to San Rafael within the larger framework of District III, this research presents a refined model for food terminal development that balances logistical precision with accessibility and stakeholder participation. The recommendations propose strategies to enhance infrastructure adaptability, refine planning methodologies, and strengthen multi-sectoral integration to support sustainable food terminal operations.